Integrating Unique Identification Numbers in Civil Registration - World Bank (World Bank, Washington, DC, 2018)
The objective of this report is to examine the process for assigning UINs (unique identification number) at birth and the mechanism for incorporating them into the civil register and including them on the physical birth certificate. This report will discuss the CRS (civil registration system) and the practical steps necessary to ensure a system that can establish the identity of a person and issue a trusted certificate to attest to his or her civil status. Although it may serve as a reference for country-specific discussions, the overarching issues are universal. This report is divided into three main sections : 1) Description of the process flow associated with CR (civil registration), with emphasis on birth registration, to lay out a generic set of processes needed for any system, Description and analysis of UIN structures and 2) Overview, description and analysis of UIN structures, followed by use cases. 3) Description of necessary steps and good practices for linking CRS with CIS (civil identification system), using UINs as a common denominator.